The Social and Political Ideas of Some Great Thinkers of the Sixteenth and Seventeenth Centuries : A Series of Lectures Delivered at King's College University of London During the Session 1925-26 - Hearnshaw, F.J. C. (1967)
Estudio que interpreta las ideas políticas y sociales de 8 pensadores del siglo XVI y XVII: Jean Bodin, Richard Hooker, Francisco Suárez, Jaime I, Rey de Inglaterra, Hugo Grocio, Thomas Hobbes, James Harrington y Baruch Spinoza.